PENGARUH IMPLEMENTASI CORPORTATE SOCIAL RESPONSIBILITY TERHADAP HARGA SAHAM (Studi pada Emiten LQ45 di Bursa Efek Indonesia Tahun 2006/2007) - Solihin Solihin; Wibowo Wibowo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2012)
This research is purposed to determine influence CSR disclosure to stock price of banking and mining companies that listed at Indonesia Stock Exchange(IDX). There are two model ofresearch, the first model without control variable BETA and PBV. The second model included control variable BETA and PBV. BETA is proxy of risk and PBV is proxy of growth. This research was conducted on 30 mining and banking companies that listed in Indonesia Stock Exchange (IDA9 for the period 2006-2007. The method which used to select sample ofthis research is purposive sampling. Data analysis methods used Pearson for validity test, P-P Plot for normality test, Variance Inflation Factor(VIF) for multicollinearity test, LM-test for autocorrelation, and Glejser for heterrocedacity test. 7.= test and F-test was used to test hypothesis. The result of this research are in the first model( without control variable BETA and PBV), CSRI disclosure, Unexpected Return(UE), interaction between CSRI & UE not influenced CAR of mining and banking companies that listed at IDX. The second model(included control variable BETA and PBV) indicated that CSRI disclosure, Unexpected Return(UE), interaction between CSRI & UE, Price to Book Value(PBIO, BETA, interaction BETA & PBVnot influenced CAR ofbanking and mining companies that listed at IDX